2008
DOI: 10.1158/1078-0432.ccr-08-0315
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Copper-Binding Agent ATN-224 in Patients with Advanced Solid Tumors

Abstract: Purpose: Copper chelation reduces the secretion of many angiogenic factors and reduces tumor growth and microvascular density in animal models. ATN-224 is a second-generation analogue of ammonium tetrathiomolybdate. The aim of our phase I study was to reduce serum copper levels, as measured by ceruloplasmin, to 5 to 15 mg/dL (normal 16-60) in 14 to 21days, to determine the pharmacokinetic profile of ATN-224 and to evaluate dose-limiting toxicities. Patients and Methods: Cohorts of patients were treated with es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
74
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 26 publications
1
74
0
Order By: Relevance
“…In addition, the copper chelator ATN-224, which interferes with the activation of SOD1 (and other cellular processes), inhibits growth of tumor cells and blocks angiogenesis in animal models (15), suggesting a role for SOD1 in regulating tumorigenesis and angiogenesis. ATN-224 is currently being tested in clinical trials for the treatment of late stage solid tumors (16). However, there has been no clear evidence pointing to a specific role for SOD1 in tumorigenesis, and we are unaware of any previously reported SOD1 inhibitors known to be effective in cells, other than copper chelators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the copper chelator ATN-224, which interferes with the activation of SOD1 (and other cellular processes), inhibits growth of tumor cells and blocks angiogenesis in animal models (15), suggesting a role for SOD1 in regulating tumorigenesis and angiogenesis. ATN-224 is currently being tested in clinical trials for the treatment of late stage solid tumors (16). However, there has been no clear evidence pointing to a specific role for SOD1 in tumorigenesis, and we are unaware of any previously reported SOD1 inhibitors known to be effective in cells, other than copper chelators.…”
Section: Discussionmentioning
confidence: 99%
“…The SOD activity can be measured in blood pellets and tumour lysates, and is quickly inhibited upon ATN-224 dosing. The PK of ATN-224 is followed by tracking Mo in plasma (Berenson et al, 2006;Lowndes et al, 2006). This approach, however, does not distinguish the active compound from its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that longer treatments than those used in this study may lower the threshold of ATN-224 needed for inhibiting blood cell SOD1. Indeed, data from a phase I trial showed a profound and persistent inhibition of SOD1 in blood pellets in patients treated at several ATN-224 doses below and at the maximal tolerated dose (Lowndes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations